Impacts of Rodenticide and Insecticide Toxicants from Marijuana Cultivation Sites on Fisher Survival Rates in the Sierra National Forest, California. Issue 2 (18th June 2013) - Thompson, Craig; Sweitzer, Richard; Gabriel, Mourad; Purcell, Kathryn; Barrett, Reginald; Poppenga, Robert
Abstract Secondary exposure of wildlife to pesticides has been well documented, yet exposure is typically associated with agricultural or wildland‐urban interface areas. Wildlife in undeveloped areas is generally presumed free from risk. In 2009, a male fisher was found dead in the Sierra National Forest and subsequent necropsy revealed that the animal died of acute rodenticide poisoning. Follow‐up testing revealed that 85% of fisher carcasses recovered by two research projects in the previous three years tested positive for rodenticides. Concern arose that exposure could predispose an animal to mortality from other causes, and that the underlying role of toxicants would escape notice. Further investigation indicated that the most likely source was the numerous illegal marijuana cultivation sites currently found on public lands throughout the western United States. To determine whether the presence of cultivation sites predisposed fishers to mortality from other sources, we related survival rates to the presence and number of cultivation sites found within that animal's home range over the past 10 years. Likelihood of exposure was related to the presence of cultivation sites, and female fisher survival was influenced by the number of cultivation sites within its home range. We discuss the conservation implications of this unexpected relationship.